Immobilized Ru-Pincer Complexes for Continuous Gas-Phase Low-Temperature Methanol Reforming-Improving the Activity by a Second Ru-Complex and Variation of Hydroxide Additives - Schwarz, Christian; Kraus, Dominik; Alberico, Elisabetta; Junge, Henrik; Haumann, Marco (European Journal of Inorganic Chemistry, 2021)
Ru-pincer complexes were immobilized as supported liquid phase (SLP) materials to allow the methanol reforming reaction as continuous gas phase process. Under reaction conditions, the liquid phase forms from the hydroxide coating. Several hydroxides were screened and CsOH showed highest activity compared to the standard KOH coating. The well-known Ru-pincer complex carbonylchlorohydrido [bis(2-di-i-propylphosphinoethyl)amine]ruthenium(II) is limited in catalyzing the final step of the methanol reforming. Addition of a second complex, having a methylated backbone in the pincer-ligand, could overcome these limitations. Significant enhancement of the overall catalytic activity was observed.
CRIS-Team WoS Importer:2021-05-28